RELATIONSHIP OF SERUM PROGESTERONE PROFILES BEFORE, DURING AND AFTER OESTRUS AND ESTABLISHMENT OF PREGNANCY IN REPEAT BREEDER COWS - Selvaraju, M; Veerapandian, C; Kathiresan, D; Kulaseka, K; Chandrahasan, C (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted to study the effect of progesterone before, during and after AI in repeat breeder crossbred cows. A total of 16 repeat breeder cows were artificially inseminated twice at 24 hours interval following sexual rest of one oestrous cycle. Blood samples were collected from all the cows on day 10 of oestrous cycle preceding AI, at the time of first AI (oestrus) and at second, fourth and 6th day following first AI for progesterone assay. The first service conception rate observed was 18.75 per cent. The mean serum progesterone levels on corresponding days of blood collection in cows which became pregnant was 7.19±0.46, 0.36±0.08, 1.05±0.20, 1.70±0.22 and 3.37±0.77 ng/ml, respectively and the values in cows which did not conceive were 5.24±0.43, 0.51±0.09, 0.57±0.15, 0.99±0.27 and 1.62±0.26 ng/ml.